Pengaruh Kecerdasan Emosional dan Stres Kerja terhadap Kinerja Pegawai Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah Kota Binjai - Aliansyah, Rafli; Bahtiar, Bahtiar; Sonata, Ilham (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
The formulation of the problem in this study is how the influence of emotional intelligence on employee performance. How work stress affects employee performance. How emotional intelligence and job stress affect employee performance. The purpose of this study is to determine the effect of emotional intelligence on employee performance To determine the effect of emotional intelligence on employee performance. To determine the effect of emotional intelligence and work stress on employee performance. The sample in this study amounted to 87 people. Data collection techniques in this study used questionnaires, interviews, observations, and literature studies. The analytical techniques used in this study use data quality test techniques, classical assumption tests, multiple linear analysis. The results of this study show that emotional intelligence partially has a positive and significant effect on employee performance, work stress partially has a positive and significant effect on employee performance, emotional intelligence and work stress simultaneously have a positive and significant effect on employee performance